DriftScalarDyFoam: An OpenFOAM-Based Multistage Solver for Drifting Snow and Its Distribution Around Buildings - Chen, Xiaoxiao; Yu, Zhixiang (Frontiers in Earth Science, 2022)
There is a complex coupling relationship between the airflow and snow cover. In a period of hours or even days, the airflow will cause the redistribution of snow, and the redistribution of snow will cause the airflow to change. This study develops a dynamic mesh technology applied in snow drifting simulation through a real-time dynamic mesh update to depict the snow surface evolution process under long-period snow drifting, and a solver application named driftScalarDyFoam based on OpenFOAM is implemented. This solver divides the long-period snow drifting process into several stages, in each of which a snow transport equation is applied to predict the spatial distribution of snow, and finally, the snow surface evolves according to the erosion–deposition model. This method that we have proposed has been validated for several measured cases, including snow distribution on a flat roof and snow distribution around a building.